Corrosion Inhibition of Mild Steel using Potato Peel Extract in 2M HCl Solution - Ibrahim, Taleb (2011)
The inhibitive effect of naturally available potato peel extract (PPE) toward the corrosion of mild steel in 2M HCl solution has been investigated by weight loss and electrochemical techniques. The results showed increase in the inhibition efficiency with increasing potato peels extract concentration. A reasonable corrosion inhibition level was obtained at a concentration of 50 ppm (>70% inhibition efficiency). Nyquist plots from Impedance data showed that upon increasing the PPE concentration, the charge transfer resistance increased and the doubled layer capacitance decreased. The adsorption film of extract on the mild steel specimen was also found to follow Langmuir adsorption isotherm.